Association between Air Pollutants and Asthma Emergency Room Visits and Hospital Admissions in Time Series Studies: A Systematic Review and Meta-Analysis - Zheng, Xue-yan; Ding, Hong; Jiang, Li-na; Chen, Shao-wei; Zheng, Jin-ping; Qiu, Min; Zhou, Ying-xue; Chen, Qing; Guan, Wei-jie (PloS one, 2015)
Air pollution constitutes a significant stimulus of asthma exacerbations; however, the impacts of exposure to major air pollutants on asthma-related hospital admissions and emergency room visits (ERVs) have not been fully determined. We sought to quantify the associations between short-term exposure to air pollutants [ozone (O3), carbon monoxide (CO), nitrogen dioxide (NO2), sulfur dioxide (SO2), and particulate matter ≤10 μm (PM10) and PM2.5] and the asthma-related emergency room visits (ERV) and hospitalizations. Systematic computerized searches without language limitation were performed. Pooled relative risks (RRs) and 95% confidence intervals (95%CIs) were estimated using the random-effect models. Sensitivity analyses and subgroup analyses were also performed. After screening of 246 studies, 87 were included in our analyses. Air pollutants were associated with significantly increased risks of asthma ERVs and hospitalizations [O3: RR(95%CI), 1.009 (1.006, 1.011); I2 = 87.8%, population-attributable fraction (PAF) (95%CI): 0.8 (0.6, 1.1); CO: RR(95%CI), 1.045 (1.029, 1.061); I2 = 85.7%, PAF (95%CI): 4.3 (2.8, 5.7); NO2: RR(95%CI), 1.018 (1.014, 1.022); I2 = 87.6%, PAF (95%CI): 1.8 (1.4, 2.2); SO2: RR(95%CI), 1.011 (1.007, 1.015); I2 = 77.1%, PAF (95%CI): 1.1 (0.7, 1.5); PM10: RR(95%CI), 1.010 (1.008, 1.013); I2 = 69.1%, PAF (95%CI): 1.1 (0.8, 1.3); PM2.5: RR(95%CI), 1.023 (1.015, 1.031); I2 = 82.8%, PAF (95%CI): 2.3 (1.5, 3.1)]. Sensitivity analyses yielded compatible findings as compared with the overall analyses without publication bias. Stronger associations were found in hospitalized males, children and elderly patients in warm seasons with lag of 2 days or greater. Short-term exposures to air pollutants account for increased risks of asthma-related ERVs and hospitalizations that constitute a considerable healthcare utilization and socioeconomic burden.